Peculiarities of distributed systems, SCADA and IoT - Simeonova, Tsvetelina (Yearbook Telecommunications, 2021)
The aim of the work is to consider and compare the features of distributed systems, SCADA and IIoT. Both SCADA and IoT include sensors and data collection. Although they differ in many respects, they share a common goal. The idea of a smart grid leads to the integration of SCADA and IoT. SCADA is useful for monitoring and managing installations or industrial equipment. The Internet of Things is a collection of physical devices with different implementations, software upgrades, sensors, actuators, and network connectivity, all of which work together to enable objects to connect and exchange data. The focus of the article is the consideration, as distributed systems and in comparative terms, of the development of industrial technologies IoT and SCADA. The presentation will include a summary of the characteristics of these two technologies and a structural-functional analysis of the efficiency in the integration of the latest generations of SCADA systems in the functionality of IoT. The possibilities for integration are shown, as well as the prerequisites for this. The results can be used as recommendations in the areas of design and operation.